Effect of ammonium nitrate and combustible binder on the ignition characteristics of high-energy materials containing aluminum borides - Korotkikh, Alexander G. (Combustion, explosion, and shock waves)
This paper presents the results of an experimental study of the processes of thermal decomposition and ignition of high-energy materials (HEMs) containing an oxidizer, a combustible binder, and dispersed additives of aluminum, aluminum borides (AlB2 and AlB12), and amorphous boron. A Netzsch STA 449 F3 Jupiter thermal analyzer and an experimental testbed, which includes a continuous-wave CO2 laser, are used to investigate the response and ignition characteristics of two basic HEM compositions based on AP/SKDM/Me and AP/AN/MPVT/Me at different heating rates. It is revealed that ammonium nitrate at low heat flux densities (q < 130 W/cm(2)) decomposes and melts, forming a liquid layer on the reaction surface and increasing the delay time of the emergence of a HEM flame containing Al, AlB2, and AlB12. As the heat flux density becomes higher, the effect of the liquid layer on the reaction surface of the sample decreases due to an increase in the surface temperature, the outflow rate of gaseous decomposition products, and the layer evaporation.